The Religious Freedom: Universalism Claim, Resistance of Islamic World, and Reconceptualization - Fawaizul Umam (UIN Sunan Kalijaga Yogyakarta, 2020)
AbstractReligious freedom is one type of human rights which caused major resistance to the universalism claim of human rights in Muslim countries. This article attempted to describe why that resistance arose and how Islam should reconceptualize religious freedom. The religious freedom issues are important to be explored in the context of contemporary Islamic studies because its value and scope tended to be limited in the Islamic conservatism discourse. One of the issues is the fallacy in categorizing the apostasy (riddah)—a non-derogable right—verdicted as a blasphemy in Islam. By reconceptualizing the Islamic meaning of religious freedom, this study applied document analysis to enrich the contemporary Islamist studies, especially to postulate the significant relationship between Islam and human rights and to argue that Islam actually legitimized religious freedom as one of the non-derogable rights.